Symptoms and Treatment-Related Knowledge of Cancer Patients Receiving Chemotherapy) - Nawaz Ali, Kiran; Shah, Ibrahim (Riviera Publishing, 2023)
This study aims to investigate the existing level of knowledge regarding the symptoms, side effects, and treatment plans of cancer patients undergoing chemotherapy. Addressing gaps in literature and enhancing patient education can significantly improve outcomes and reduce cancer-related mortality and morbidity worldwide. Several search engines, including PubMed, CINHAAL, Science Direct, Research Gate, and Google Scholar, were used to conduct a comprehensive and broad literature evaluation. Each database was searched using keywords for